Study of pragmatic analysis of literature on the development of ELT students’ receptive and productive skills: A case of North Cyprus - Ebru Munir; Mehmet Ali Yavuz (Heliyon)
Language serves as a mirror reflecting our understanding of the world and mirrors the world of literature. Pragmatics extends beyond mere literal interpretation, delving into comprehending subtle implications, varying expressions and lexical ambiguities. This deepens our exploration and appreciation of the world of literature. It is worth investigating whether pragmatic instruction can improve students' language awareness and competence. To this end, a quasi-experimental study involving the students of two English language teaching (ELT) classes was conducted to determine whether pragmatic treatment could enhance students' comprehension skills and to identify how effectively the pragmatic understanding of literature through Shakespeare's language could aid the development of receptive and productive skills in ELT students. Participants took two pre-tests: multiple-choice discourse completion task (MCDCT) and discourse completion task (DCT) based on Othello. After the treatment, the same tests were administered as post-tests. Results showed that the experimental group outperformed the control group in comprehension skills. Cohen's D effect size calculation confirmed the practical usefulness of the treatment and the significant difference between the two groups. The study concludes that pragmatic training using literary texts contributes to developing ELT students' pragmatic competence.